Cerebral atrophy and nephropathic cystinosis. Issue 4 (April 1986) - Cochat, P; Drachman, R; Gagnadoux, M F; Pariente, D; Broyer, M
Abstract : The management of end stage renal failure in cystinotic children is correlated with a longer survival, sometimes complicated with neurological abnormalities. Cranial computed tomography was performed in 10 patients and showed a significant atrophy; the pathogenesis of this damage remains unclear.